16th IHIW : Review of HLA typing by NGS. (9th January 2013) - De, D.; Dinauer, D.; Duke, J.; Erlich, H. A.; Holcomb, C. L.; Lind, C.; Mackiewicz, K.; Monos, D.; Moudgil, A.; Norman, P.; Parham, P.; Sasson, A.; et al.
Summary Human leucocyte antigen (HLA) genes play an important role in the success of organ transplantation and are associated with autoimmune and infectious diseases. Current DNA‐based genotyping methods, including Sanger sequence‐based typing (SSBT), have identified a high degree of polymorphism. This level of polymorphism makes high‐resolution HLA genotyping challenging, resulting in ambiguous typing results due to an inability to resolve phase and/or defining polymorphisms lying outside the region amplified. Next‐generation sequencing (NGS) may resolve the issue through the combination of clonal amplification, which provides phase information, and the ability to sequence larger regions of genes, including introns, without the additional effort or cost associated with current methods. The NGS HLA sequencing project of the 16IHIW aimed to discuss the different approaches to (i) template preparation including short‐ and long‐range PCR amplicons, exome capture and whole genome; (ii) sequencing platforms, including GS 454 FLX, Ion Torrent PGM, Illumina MiSeq/HiSeq and Pacific Biosciences SMRT; (iii) data analysis, specifically allele‐calling software. The pilot studies presented at the workshop demonstrated that although individual sequencers have very different performance characteristics, all produced sequence data suitable for the resolution of HLA genotyping ambiguities. The developments presented at this workshop clearly highlight the potential benefits of NGS in the HLA laboratory.